Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Solve the SDE: $dX(t) = udt + \sigma X(t)dB(t)$

Provided Question

The SDE is $dX(t) = udt + \sigma X(t)dB(t)$. Find $X(t)$, where $X(t)$ is some stochastic process and $B(t)$ is a Wiener process. Both $u$ and $\sigma$ are constants.

Hint: Multiply both sides by the "integrating factor" $e^{-\sigma B(t) + \frac12 \sigma^2 t}$.

Current Progress

Multiplying both sides by the appropriate integrating factor:

$$ \exp{\big( -\sigma B(t) + \frac12 \sigma^2t\big)}dX(t) = \exp{\big(-\sigma B(t)+\frac12\sigma^2t\big)}(udt + \sigma X(t)dB(t)) $$

Then set $f(t,x,b):=\exp{\big( -\sigma B(t) + \frac12 \sigma^2t\big)}X(t)$ and apply Ito's formula. Some of the required results before actually applying Ito's formula:

$ \frac{df}{dt} = \frac12\sigma^2 X(t)e^{-\sigma B(t) + \frac12 \sigma^2t} \\ \frac{df}{dx} = e^{-\sigma B(t) + \frac12 \sigma^2t} \\ \frac{df}{db} = -\sigma X(t)e^{-\sigma B(t) + \frac12 \sigma^2t} \\ \frac{d^2f}{dx^2} = 0 \\ \frac{d^2f}{db^2} = \sigma^2 X(t) e^{-\sigma B(t) + \frac12 \sigma^2t} \\ \frac{d^2f}{dxdb} = -\sigma e^{-\sigma B(t) + \frac12 \sigma^2t} $

Given this, we need to know the following derivatives of the quadratic variations and co-variations:

$ d\langle B\rangle_t = dt \\ d\langle X,B\rangle_t = ??? $

My Request

Please instruct me on what $d\langle X,B\rangle_t$ is equal to so that I may progress further with this problem.

share|improve this question
1  
$d\langle X,B\rangle_t = \sigma X dt$, in general for 2 stoch.int. $\int h dB, \int g dB$ the QcoV is $gh dt$ –  mike Nov 9 '12 at 19:00
    
@mike That makes complete sense. But, are you 100% sure this is accurate in this instance? –  Jase Nov 10 '12 at 3:31
    
this is prop ix.2.3 in revuz & yor. $e = \frac 1 f$ is a martingale that satisfies $de = edB$. I don't think you ever need $d \langle X,B \rangle$ bt I'm pretty sure about it. –  mike Nov 10 '12 at 14:46

1 Answer 1

up vote 5 down vote accepted

As mike already wrote: $<X,B>_t = \sigma \cdot X_t \, dt$ - this fact follows straight from the definition of $<\cdot,\cdot>$.

Another approach to solve the SDE:

  1. Solve the homogeneous SDE $dX_t = \sigma \cdot X_t \, dB_t$. Idea: Set $Z_t := \log X_t$ and apply Itô's formula to $f(x) := \log x$, then $$dZ_t = \frac{1}{X_t} \, dX_t - \frac{1}{2} \frac{1}{(X_t)^2} (dX_t)^2 = \left(- \frac{1}{2} \sigma^2 \right) \, dt + \sigma dB_t \\ \Rightarrow X_t = X_0 \cdot \exp \left(- \int_0^t \frac{1}{2} \sigma^2 \, ds \right) \cdot \exp \left(\int_0^t \sigma \, dB_s \right) = X_0 \cdot \exp \left(- \frac{1}{2} \sigma^2 \cdot t + \sigma \cdot B_t \right)$$
  2. Solve the inhomogeneous SDE: Let $$X_t^0 := \exp \left( \frac{1}{2} \sigma^2 \cdot t - \sigma \cdot B_t \right)$$ then we know that $\frac{1}{X_t^0}$ solves the homogeneous equation (and $X_0^0=1$). Now set $Z_t := X_t \cdot X_t^0$ and apply Itô's formula to $f(x,y) = x \cdot y$, then $$dZ_t = \ldots = u \cdot X_t^0 \, dt$$ thus $$X_t = \frac{Z_t}{X_t^0} = \frac{u \cdot \int_0^t \exp \left( \frac{1}{2} \sigma^2 \cdot t - \sigma \cdot B_t\right) \, dt}{\exp \left( \frac{1}{2} \sigma^2 \cdot t - \sigma \cdot B_t\right)}$$

This approach also works in a similar way for the SDE

$$dX_t = (a(t)+b(t) \cdot X_t) \, dt + (c(t)+d(t) \cdot X_t) \, dB_t$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.